Addressing Country-Level Fiscal and Financial Sector Vulnerabilities : An Evaluation of the World Bank Group’s Contributions - Independent Evaluation Group (World Bank, Washington, DC, 2021)
More than a decade has passed since the global economic and financial crisis rocked the world. A clear lesson that emerged from it was the importance of identifying and addressing country-specific vulnerabilities ex ante to build resilience when a shock occurs. The 2020 global economic and health crisis caused by COVID-19 serves as a yet another stark reminder of the importance of proactively managing vulnerabilities to shocks. The purpose of this evaluation is to assess World Bank Group support to client countries to build resilience to exogenous shocks through the systematic identification of fiscal and financial sector vulnerabilities and through efforts to support the reduction of these vulnerabilities. Given the importance of protecting the most vulnerable from shocks, this evaluation also looks at the extent to which the Bank Group has helped client countries adapt their social safety nets so that they can be effectively scaled up in a crisis. It aims to inform the design of future Bank Group strategies, operations, diagnostics, and knowledge products that can help reduce country-level fiscal and financial sector vulnerabilities. Its lessons may also help the effort to “build back better” after the COVID-19 pandemic through contributions to increasing resilience by strengthening fiscal and financial buffers and institutions.